2010
DOI: 10.1158/0008-5472.can-10-1242
|View full text |Cite
|
Sign up to set email alerts
|

Hippo Pathway Effector Yap Is an Ovarian Cancer Oncogene

Abstract: The Hippo pathway regulates organ size and tumorigenesis in Drosophila and mammals and is altered in a variety of human cancers, yet it remains unclear if the Hippo pathway is of prognostic significance to cancer patients. Here we show that the key targets of Hippo signaling, transcriptional coactivators Yki and Yap, play a conserved role in promoting ovarian cancer in flies and humans, respectively. Whereas studies linking Yap to cancer in other tissues have focused on overall Yap levels, we show for the firs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
208
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(219 citation statements)
references
References 24 publications
4
208
0
7
Order By: Relevance
“…Huang et al reported that knockdown of YAP significantly increased EGFRI erlotinib sensitivity in ovarian cancer cell lines that express little or no TAZ (21). In addition, knockdown of YAP in ovarian cancer cell lines that express both YAP and TAZ only led to a very moderate effect on cancer cell growth or drug sensitivity (22,23). Here, we have shown that knockdown of TAZ in breast cancer cell lines that express little or no YAP, such as BT-549 cells, increased EGFRI sensitivity; however, for breast cancer cell lines that express both YAP and TAZ, such as MDA-MB-231 cells, knockdown of TAZ may not help improve sensitivity of EGFRI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al reported that knockdown of YAP significantly increased EGFRI erlotinib sensitivity in ovarian cancer cell lines that express little or no TAZ (21). In addition, knockdown of YAP in ovarian cancer cell lines that express both YAP and TAZ only led to a very moderate effect on cancer cell growth or drug sensitivity (22,23). Here, we have shown that knockdown of TAZ in breast cancer cell lines that express little or no YAP, such as BT-549 cells, increased EGFRI sensitivity; however, for breast cancer cell lines that express both YAP and TAZ, such as MDA-MB-231 cells, knockdown of TAZ may not help improve sensitivity of EGFRI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, sustained YAP overexpression eventually leads to formation of tumors characteristic of hepatocellular carcinoma (HCC) (Dong et al, 2007). Furthermore, genomic amplification and elevated expression and nuclear localization of YAP has been observed in human cancers (Overholtzer et al, 2006;Zender et al, 2006;Dong et al, 2007;Zhao et al, 2007;Steinhardt et al, 2008;Hall et al, 2010). Overexpression of TAZ has also been noted in human breast cancer samples and non-small cell lung cancer cell lines (Chan et al, 2008;Zhou et al, 2011b).…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 99%
“…YAP, a mammalian homolog of Drosophila Yorkie), a key effector of this pathway, promotes EMT and cell motility in vitro (Overholtzer et al 2006;Zhao et al 2008a;Zhang et al 2009). Furthermore, abnormal YAP activity associates with poor survival of ovarian cancer patients significantly (Hall et al 2010;Zhang et al 2011b). These results drew our attention to investigate roles of the Hippo pathway in cell migration.…”
mentioning
confidence: 91%